2000
DOI: 10.1046/j.1365-2249.2000.01214.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine specificity of autoantibodies to calreticulin: epitope mapping and characterization

Abstract: SUMMARYExtracellular calreticulin (CRT) as well as anti-CRT antibodies have been reported in patients with various autoimmune disorders and CRT has been implicated in`epitope spreading' to other autoantigens such as the Ro/SS-A complex. In addition, antibodies against parasite forms of the endoplasmic reticulum chaperone, CRT, have been found in patients suffering from onchocerciasis and schistosomiasis. In this study, we screened sera for anti-CRT antibodies from patients with active and inactive systemic lup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…Interestingly, the surface blebs of apoptotic keratinocytes bind C1q, an early component of the complement cascade (132). The only C1q binding protein that has been identified in apoptotic blebs to date is calreticulin (98) and autoantibodies to calreticulin can interfere with this binding (133). The binding of C1q to apoptotic cells has been postulated to facilitate the clearance of these cells by macrophages, which express a C1q cell surface receptor (134,135).…”
Section: Abnormal Clearance Of Apoptotic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the surface blebs of apoptotic keratinocytes bind C1q, an early component of the complement cascade (132). The only C1q binding protein that has been identified in apoptotic blebs to date is calreticulin (98) and autoantibodies to calreticulin can interfere with this binding (133). The binding of C1q to apoptotic cells has been postulated to facilitate the clearance of these cells by macrophages, which express a C1q cell surface receptor (134,135).…”
Section: Abnormal Clearance Of Apoptotic Cellsmentioning
confidence: 99%
“…The identification of a dominant grp78 binding motif on Ro52 (178) and the coexistence of grp78, Ro52 and Ro60 in the surface membrane blebs of apoptotic cells (98) support this view. Interestingly, autoantibodies directed towards grp94/gp96 and calreticulin have also been detected in the sera of patients with SLE (133,179,180) and could perhaps be generated via a similar mechanism.…”
mentioning
confidence: 99%
“…Analyses of the reactivity of specific antibody isotypes against these peptides were aimed to identify relevant B cell epitopes that could be used in a subunit vaccine (Joshi et al 2000, Tallima et al 2003. Synthetic peptides have been widely used for the evaluation of both B and T cell epitopes responsible for (or that could lead to) protection against other pathogens, including Schistosoma (Reynolds et al 1992, 1994, Eggleton et al 2000, Joshi et al 2000. We demonstrated that BALB/c mice vaccinated with SmCT-SOD developed high levels of antibodies directed mainly to the SmCT-SOD derived peptide 3 (Pep 3), which included amino acid residues 64-83 .…”
Section: Identification Of Parasite-specific Epitopesmentioning
confidence: 99%
“…8,9 The various mechanisms contributing to intracellular CRT delocalization and the effects of CRT presentation on the cell surface for induction of immunogenic cell death and apoptosis recently have been studied intensely. [8][9][10] In contrast, the extracellular expression and regulation of CRT are poorly understood. In this report, we investigated the regulation and function of CRT in the serum of patients with AML.…”
Section: Introductionmentioning
confidence: 99%